PENERAPAN MODEL PEMBELAJARAN QUANTUM TEACHING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS IX.5 SMP NEGERI 8 PEKANBARU - Etika Pujiati Pujiati; Elfis Suanto Suanto; Sakur ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research is classroom action research that aims to improve learning process and to increase mathematics achievement with applied the learning model of Quantum Teaching. The subject of this research is student of class IX.5 SMPN 8 Pekanbaru in the first semester academic years 2014/2015, which amounted to 34 students, consist of 17 boys and 17 girls. The research consisit of two cycles, each cycle has four stages, which are planning, implementation, observation, and reflection. At the end of every cycle daily exams will be implemented. Data collection is done by observation and tests in the form of daily tests. The result of research shows that implementation of learning process on cycle II had happened improvement from implementation on cycle I. Weakness on cycle I is improved on implementation cycle II according with planning of improvement after reflection cycle I. Most of students were excited and active in learning process, such as while they were presenting questions and giving the conclusion of learning. Number of students that reach Minimum Mastery Criteria increase from basic score to daily tests I and II. The number percentage of students who reach Minimum Mastery Criteria on basic, daily test I and daily test II  are respectively 52.94%, 61.76%, and 82.35%. Results of this research indicates that appication of the learning model of Quantum Teaching can improve learning process and increase mathematics achievement from the students at class IX.5 SMPN 8 Pekanbaru in the first semester academic years 2014/2015. Key Words: Mathematics Achievement, Quantum Teaching, Class Action Research